A review of advancements of artificial intelligence in dentistry - Maryam Ghaffari; Yi Zhu; Annie Shrestha (Elsevier, 2024)
Artificial intelligence (AI) has been used in healthcare for decades and has the potential to revolutionize dentistry by solving multiple clinical problems and making the work of clinicians easier. In particular, the study of AI applications in periodontal disease and cariology is important because these are two major areas of concern in dental health. Periodontal disease, which affects the gums and bone surrounding the teeth, is a major cause of tooth loss in adults. Cariology, the study of dental decay, is also an important area of focus for AI research. AI algorithms can be used to analyze dental images and detect early signs of decay that may be missed by human dentists. The review first discusses the history of AI in healthcare and then highlights some of the ways technology has improved dentistry and then describe some basic AI models such as artificial neural networks (ANNs), convolutional neural networks (CNNs), and random forest. The article then delves into how AI is involved in periodontal disease, cariology, endodontics, prosthodontics, and orthodontics including classifying different types of periodontal disease, identifying areas of bone loss, determining the severity of the disease, analyzing dental images, and detecting early signs of diseases. On the other hand, the application of AI in dentistry is relatively uncommon because implementing AI technologies in dentistry presents several challenges that need to be addressed for successful implementation of AI technologies in dentistry.